Frequency of somatic mutations in TERT promoter, TP53 and CTNNB1 genes in patients with hepatocellular carcinoma from Southern Italy - Lombardo, Daniele (Oncol Lett, 2020)
Somatic mutations in the TERT promoter and in the TP53 and CTNNB1 genes are considered drivers for hepatocellular carcinoma (HCC) development. They show variable frequencies in different geographic areas, possibly depending on liver disease etiology and environmental factors. TP53, CTNNB1 and TERT genetic mutations were investigated in tumor and non-tumor liver tissues from 67 patients with HCC and liver tissue specimens from 41 control obese subjects from Southern Italy. Furthermore, TERT expression was assessed by reverse transcription-quantitative PCR. Neither CTNNB1 mutations or TP53 R249S substitution were detected in any case. The TP53 R72P polymorphism was found in 10/67 (14.9%) tumors, but was not found in either non-tumor tissues (P=0.001) or controls (P=0.009). TERT gene promoter mutations were found in 29/67 (43.3%) tumor tissues but were not found in either non-tumor (P<0.0001) or control liver specimens (P<0.0001). The most frequent mutation in the tumors was the known hot spot at −124 bp from the TERT ATG start site (−124G>A, 28 cases, 41.8%; P<0.0001). A new previously never reported TERT promoter mutation (at −297 bp from the ATG, −297C>T) was found in 5/67 (7.5%) tumors, in 0/67 (0%) non-tumor (P<0.0001), and in 0/41 (0%) controls (P=0.07). This mutation creates an AP2 consensus sequence, and was found alone (1 case) or in combination (4 cases) with the −124 bp mutation. The mutation at −124 and −297 bp induced a 33-fold (P<0.0001) and 40-fold increase of TERT expression levels, respectively. When both mutations were present, TERT expression levels were increased >300-fold (P=0.001). A new TERT promoter mutation was identified, which generates a de novo binding motif for AP2 transcription factors, and which significantly increases TERT promoter transcriptional activity.